INTERVIEW WITH ARCHITECT PHILIPPE RAHM. Imagination without scientific knowledge is weak - Krstić, Verica S; Kordić, Milena T; Ristić Trajković, Jelena M (Arhitektura i urbanizam, 2015)
The problems of relations between people and the environment, and changes of these relations, are essential for practice of architectural design. As Van der Ryn and Cowan claim: In many ways,  the environmental crisis is a design crisis. Design reflects culture, and the culture rests on what we believe to be true about the world (Van der Ryn, Cowan, 2007:6). In line with concern about global warming, climate change and sustainable development (the Brandt Commission, 1982 Brundtland Commission, 1987, Rio de Janeiro, 1992) ecological architecture is developed in the last few decades, from Energy efficiency design towards Sustainable design. Contemporary architectural practice usually approaches these problems in terms of technological and scientific aspects, in order to protect the environment and reduce energy consumption, while architectural typologies and design methodologies remain unchanged. In order to improve not only quantitative but also qualitative characteristics of the space, it is necessary to rethink and redefine forms of relationship between architecture and nature, typology and methodology of architectural design in accordance with contemporary environmental and ecological approaches. Architectural practice of Swiss architect Philippe Rahm questions and examines these aspects of architecture. The interview shows one of the ways to offer answers to contemporary problems of relationship of man to the environment through design practice. The aim of the interview is to emphasize the need for a broader philosophical and scientific knowledge of architects-designers and to emphasize the potential of application of these specific knowledge beyond the architectural field into architectural design. The interview was held in August 2014 in English, and for the purposes of this publication has been translated into Serbian. The authors conducted interview through framework of their PHD researches. The text in English is authorized by the interviewee (architect Philippe Rahm) on 12 September 2014. The answers should present the information about the contemporary research topics in the field of architectural design.